Evaluation of oxidative stress and immunity in holstein cows supplemented with macro and trace minerals during the transition period - Marques, Raquel de Sousa (2023)
Excessive mobilization of adipose tissue during the transition period contributes to immune dysregulation and oxidative and metabolic stress. The aim of this research was to evaluate the influence of injectable mineral supplementation on oxidative stress, IgG dynamics and lipid metabolism in Holstein cows during the transition period. Healthy cows were allocated in the control group (C; n=32) or injectable mineral supplementation (SM; n=34). The animals were treated with three injections (10mL) of mineral supplement containing phosphorus, potassium, copper, magnesium and selenium intramuscularly, 30 days pre-partum, on the day of parturition and 15 days postpartum. Blood samples were collected: three weeks prepartum (M-3); two weeks prepartum (M-2); one week prepartum (M-1); in the week of delivery (M0); one week postpartum (M+1); two weeks postpartum (M+2) and three weeks postpartum (M+3). The effect of treatment, time and time * treatment interaction was determined by the MIXED procedure (PROC-mixed, SAS), and by Student’s t test for the variables that showed interaction between treatment and time. Mineral supplementation had a positive effect on the concentration of IgG in primiparous women. For multiparous women, effects of IgG and haptoglobin were observed. Similar results were observed for the total number of animals for IgG and haptoglobin. Antioxidant action of GSH was higher in treated cows for the total number of animals. It was not possible to observe a significant treatment effect for both BHB and NEFA, but the interaction between treatment and time had a significant effect for BHB in multiparous cows. The results obtained in this study suggest that the injectable supplementation protocol improved the cows’ immunity, characterized by an anti-inflammatory profile and higher serum IgG concentrations, in addition to reducing lipid metabolism and oxidative stress.